Penerapan Fuzzy Mamdani Dalam Menentukan Pencapaian Keberhasilan Mengajar Guru MI Mambaul Ulum Al-Amin Sampit - Rahmawati, R (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2021)
Current problems often do not have certain answers. The use of fuzzy mamdani logic to determine a level of achievement of the success of the teacher in teaching students at MI Mambaul Ulum Al Amin Sampit is the content of this paper. The problem will be solved by determining the level of achievement of the teacher's success in teaching students, if only two input variables are used, namely the teacher and also the value. So the first thing to solve the problem of the level of achievement of teacher success in teaching through the fuzzy mamdani method is to determine the input and output variables of a firm set. The second thing is changing the input variables into fuzzy sets through fuzzyfication. The third thing is processing data from fuzzy sets using the maximum system. The last or fourth thing is changing the results issued into a firm set through defuzzyfication with the centroid method, so the results are as desired in the output variable. The calculation of fuzzy mamdani results in an achievement level of success for MI teachers with a teacher variable value of 55 and a variable value of 80